Glutamine metabolism and radiosensitivity: Beyond the Warburg effect - Alden, Ryan S.; Kamran, Mohammad Zahid; Bashjawish, Bassel A.; Simone, Brittany A. (Frontiers in Oncology, 2022)
Mounting data suggest that cancer cell metabolism can be utilized therapeutically to halt cell proliferation, metastasis and disease progression. Radiation therapy is a critical component of cancer treatment in curative and palliative settings. The use of metabolism-based therapeutics has become increasingly popular in combination with radiotherapy to overcome radioresistance. Over the past year, a focus on glutamine metabolism in the setting of cancer therapy has emerged. In this mini-review, we discuss several important ways (DNA damage repair, oxidative stress, epigenetic modification and immune modulation) glutamine metabolism drives cancer growth and progression, and present data that inhibition of glutamine utilization can lead to radiosensitization in preclinical models. Future research is needed in the clinical realm to determine whether glutamine antagonism is a feasible synergistic therapy that can be combined with radiotherapy.